Improved spectral resolution of the femtosecond stimulated Raman spectroscopy achieved by the use of the 2nd-order diffraction method - Kang, Dong-Gu (2021)
Prolongation of the picosecond Raman pump laser pulse in the femtosecond stimulated Raman spectroscopy (FSRS) setup is essential for achieving the high spectral resolution of the time-resolved vibrational Raman spectra. In this work, the 2nd-order diffraction has been firstly employed in the double-pass grating filter technique for realizing the FSRS setup with the sub-5 cm-1 spectral resolution. It has been experimentally demonstrated that our new FSRS setup gives rise to a highly-resolved Raman spectrum of the excited trans-stilbene, which is much improved from those reported in the literatures. The spectral resolution of the present FSRS system has been estimated to be the lowest value ever reported to date, giving Δν = 2.5 cm-1.